The Theory And Practice Of Change Management - Hayes, John, 1943- (Basingstoke, Hampshire : Palgrave Macmillan, 2014)
Providing an examination of the key theoretical perspectives on organisational change, this text clearly demonstrates how the various themes can be applied within organisations to deal with the issues arising from organisational change.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Organizational change -- Management; Organizational effectiveness; Business and Management